PENDAMPINGAN UMKM DALAM MENGHADAPI TRANSFORMASI DIGITAL; PEMBUKUAN KEUANGAN DIGITAL DAN METODE PEMBAYARAN DIGITAL - Fredy Olimsar; Wirmie Eka Putra; Feny Tialonawarmi; Dios Nugraha Putra; Rofikhoh Rofikhoh (Jurnal Abdimas Bina Bangsa, 2024)
Currently is the era of digitalization where all buying and selling transactions can be carried out digitally. Based on this, there is still a lack of business actors who utilize digital sales and create digital financial reports. One of the micro and small businesses in the city of Jambi that has not yet carried out digital transformation is the Salsa 717 Kerupuk & Kemplang. Business actors still use non-digital methods in their financial bookkeeping. Therefore, this service aims to provide assistance and training in creating digital financial bookkeeping, as well as digital payment methods. Planned activities that will be implemented include providing training and direct assistance to business actors. The results of this PPM activity are: UMKM business actors can face digital transformation by implementing digital financial bookkeeping and digital payment methods, and can increase the value and quality of UMKM